THE MEANING OF METAPHOR IN SONG LYRICS PAK NGAH SUHARDI S : MAKNA METAFORA DALAM LIRIK LAGU KARYA PAK NGAH SUHARDI S - Norizan; Wahyusari, Ahada; Kurmalasari, Tety (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to describe the style of metaphor found in ten songs by Pak Ngah Suhardi S on YouTube entitled Mother, Rinduku, Rindu Ayah Bunda, Syafa'at, Kampung Halaman, Senja Dikuala Daik, Bunda Tanah Melayu, Uphold Culture, Let Love Bersemi and Pak Ngah Balek. the method used by the researcher is descriptive because the researcher wants to describe the types of metaphorical language styles found in the songs by Pak Ngah Suhardi S, the research technique that the researcher uses is a qualitative technique because the data produced is in the form of written words in the form of song lyrics by Pak Ngah Suhardi S, classifies and analyzes song lyrics. The results of this study describe the style of metaphorical language that exists in ten songs by Pak Ngah Suhardi S. The results obtained are based on the data that has been obtained, the researcher obtains seventy-nine data obtained in ten song lyrics by Pak Ngah Suhardi S. The data is divided into anthropomorphic metaphors. as many as twenty four data, then on the synesthetic metaphor there are two data and on the abstracting metaphor there are fifty three data obtained.